The Largest Stock of Guns in Canada: Charles Stark and Firearm Retailing in Late-Nineteenth-Century Toronto - Brown, R. (Ontario History, 2022)
This article examines the business of Toronto retailer Charles Stark, who in the late nineteenth century was Canada’s leading gun seller. Stark took advantage of, and encouraged, civilian interest in firearms. He emphasized the attractiveness, capabilities, and quality of modern weapons, urging customers to see firearms as consumer items that could be used for target shooting, hunting, or defence. Stark employed innovative new marketing and sales techniques. Most importantly, he produced a lengthy and beautifully illustrated catalogue by the early 1880s that preceded and dwarfed Timothy Eaton’s early catalogue business.